The age of intra-African migration: shifting patterns of regional mobility between two global diasporas, 1850–1960 - Michiel de Haas; Ewout Frankema (Comparative Migration Studies)
Abstract Rising migration out of Africa is attracting great attention among scholars, policy makers and pundits. In terms of past African mobility, forced emigration through the slave trade, with its nefarious characteristics and long-lasting legacies, has also received much publicity. But what happened to African mobility in the long century between the demise of the trans-oceanic slave trades after 1850 and the gradual resurgence of African extra-continental migration since 1960? This paper adopts the concept of the “Age of Intra-African Migration” to analyze a distinct epoch of widespread and large-scale African mobility, characterized by a succession of overlapping transitions in continent-wide migration patterns. We identify five of these transitions and explain their drivers. Overall, we show that the inward shift of African migration patterns was a consequence of intensified state formation, the demise of the transoceanic slave trades, and export-oriented commercialization. These processes were in turn shaped by trade integration, industrialization and imperialism on a global scale. As such, the Age of Intra-African Migration did not signify a retreat of Africans from global migration altogether, but rather the growing importance of migration destinations across the continent itself. We contend that the ongoing globalization of African diasporas cannot be fully understood without accounting for the dynamics of regional mobility between 1850 and 1960, and that, contrary to popular belief, Africans today are not any more mobile than they were a century ago.